Development and validation of an inflammatory bowel disease nutrition self-screening tool (IBD-NST) for digital use - Wall, Catherine L.; Wilson, Bridgette; Lomer, Miranda C. E. (Frontiers in Nutrition, 2023)
Background and aim The identification of, and timely intervention for, patients with impaired nutritional status may reduce inflammatory bowel disease (IBD) complications. This study aimed to develop and validate an IBD-specific nutrition self-screening tool (IBD-NST) that identifies patients at nutrition risk. Methods An expert IBD panel was consulted to support development of an IBD-NST. The tool was assessed in different cohorts of patients attending IBD outpatient clinics for face, content and convergent validity and repeat reliability. The tool was compared with (i) the malnutrition universal screening tool to assess face validity and (ii) subjective global assessment (SGA), hand-grip strength (HGS) and mid-arm muscle circumference to assess convergent validity. Tool content was informed by agreement between assessment tools, sensitivity analysis and chi-squared tests. The IBD-NST was completed electronically twice, 1 week apart to assess repeat reliability using observed agreement and kappa statistic. Statistical significance assumed at p < 0.05. Results In total, 282 IBD patients (175 with Crohn’s disease) were recruited to validate the IBD-NST. The final validated IBD-NST includes body mass index (BMI), weight loss and IBD-specific nutrition-focussed questions which were acceptable to patients. It identified patients at risk of malnutrition, moderately or severely malnourished patients and patients at nutritional risk. The IBD-NST identified 54/179 (30%) patients at moderate or high nutrition risk and had excellent repeat reliability in 85 patients [r = 0.77 (95% CI 0.669 to 0.746)]. Conclusion The IBD-NST is a self-screening tool, validated for use as either a paper or e-health version, that identifies patients at nutrition risk who are likely to benefit from dietetic assessment and intervention. Furthermore, patients with IBD symptoms who are concerned about their dietary intake can potentially access dietetic care more easily therefore encouraging greater self-management of IBD-related symptoms. The routine use of the IBD-NST as a self-screening tool would enable patient-led care in the outpatient setting and may facilitate timely access to dietetic care.